An association between YKL‐40 and type 2 diabetes in psychotic disorders. (17th October 2018) - Dieset, I.; Mørch, R. H.; Hope, S.; Hoseth, E.Z.; Reponen, E. J.; Gran, J. M.; Aas, M.; Michelsen, A. E.; Reichborn‐Kjennerud, T.; Nesvåg, R.; Agartz, I.; Melle, I.; et al.
Abstract : Objective: This study examines if YKL‐40 is increased in individuals with psychotic disorders and if elevated YKL‐40 levels at baseline is associated with subsequent development of type 2 diabetes. Method: A total of 1383 patients with a diagnosis of schizophrenia or affective psychosis and 799 healthy controls were recruited in the period 2002–2015. Plasma YKL‐40 and metabolic risk factors were measured and medication was recorded. Using national registry data, association between baseline risk factors and later development of type 2 diabetes was assessed using Cox proportional hazards models. Results: Plasma YKL‐40 was higher in patients vs. healthy controls also after adjusting for metabolic risk factors, with no difference between the schizophrenia and affective psychosis groups. Patients were diagnosed with type 2 diabetes at a significantly younger age. Multivariate Cox regression analyses showed that elevated YKL‐40 (hazard ratio (HR) = 5.6, P  = 0.001), elevated glucose (HR = 3.6, P  = 0.001), and schizophrenia diagnosis (HR = 3.0, P  = 0.014) at baseline were associated with subsequent development of type 2 diabetes. Conclusions: Patients with psychotic disorders have at baseline increased levels of YKL‐40 beyond the effect of comorbid type 2 diabetes and metabolic risk factors. Elevated YKL‐40 level at baseline is associated with later development of type 2 diabetes.